Implementation Of An Integrated Islamic School Network Curriculum In Strengthening Religious Character - Siregar, Bahktiar; Abd. Mukti; Siti Halima (Edukasi Islami: Jurnal Pendidikan Islam, 2023)
The aims of this research are 1) to find and describe the similarities and differences in curriculum planning for the Integrated Islamic School Network in the Formation of Religious Character at SMP It Al-Hijrah, SMP IT Jabal Noor and SMP IT AL Khansa Deli Serdang, and 2) to find and describe the similarities and differences in the implementation of the Integrated Islamic School Network curriculum in the Formation of Religious Character at SMP It Al-Hijrah, SMP IT Jabal Noor and SMP IT AL Khansa Deli Serdang. This research approach uses qualitative research. This research is classified as a type of field research, where the research objects and studies are carried out in the field. The results of this research are 1) Curriculum planning at SMP IT Al Hijrah, the curriculum is designed to not only focus on general subject matter but also intensively align Islamic values ​​into every aspect of learning. This includes not only classroom lessons but also extracurricular activities, all of which aim to support the development of consistent Islamic character. And 2) The implementation of the curriculum at SMP IT Al Hijrah includes the integration of Islamic values ​​in every subject as well as actively involving parents and the community in the educational process, creating a supportive environment. Jabal Nur IT Middle School implements a religious routine every morning and a structured Islamic Personal Development program, ensuring that Islamic character education permeates students' daily activities. At Al Khansa Khalifah IT Middle School, the focus is more on daily religious practice activities and the integration of Islamic values ​​in each subject, with extracurricular activities that support strengthening these lessons.